Esterification of Waste Cooking Oil using Heterogeneous Catalyst from Pearl Shell - Iwan Sumarlan; Rona B. Mentari (Universitas Tadulako, 2020)
Biodiesel is a renewable and environmentally friendly energy source. The process of using a homogeneous catalyst has several disadvantages, such as: removing a lot of waste water from washing the catalyst residue and cannot be reused. This catalyst is also low in corrosion and is more environmentally friendly. The purpose of this study was to study the preparation of heterogeneous catalysts from pearl shells applied to the cooking oil esterification reaction. The oil was then characterized by the XRD, XRF, SEM, and FTIR. The results of GCMS for reaction without catalysts yield only 27.07% by weight of alkyl ester, whereas using a catalyst is 93.4%. The influence of time, in the 60th minute, was the optimal time for the esterification reaction, and the effect of the weight of the catalyst which was 1% the optimal weight. This shows that pearl oyster shell catalyst can act as an esterification catalyst for used cooking oil and can be used as an alternative to a homogeneous catalyst substitute catalyst.